2019
DOI: 10.1371/journal.pone.0214338
|View full text |Cite
|
Sign up to set email alerts
|

DNA elements for constitutive androstane receptor- and pregnane X receptor-mediated regulation of bovine CYP3A28 gene

Abstract: The regulation of cytochrome P450 3A (CYP3A) enzymes is established in humans, but molecular mechanisms of its basal and xenobiotic-mediated regulation in cattle are still unknown. Here, ~10 kbp of the bovine CYP3A28 gene promoter were cloned and sequenced, and putative transcription factor binding sites were predicted. The CYP3A28 proximal promoter (PP; -284/+71 bp) contained DNA elements conserved among species. Co-transfection of bovine nuclear receptors (NRs) pregnane X and constitutive androstane receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…As expected, several genes involved in drug metabolism and transport were affected by C pretreatment, thus demonstrating how C most likely affects AFB1 uptake and biotransformation. Cattle CYP3A28 (an orthologue of human CYP3A4 and the main CYP3A isoform expressed in BFH12 cells: [117]) is a key player in AFB1 metabolism, being responsible for the synthesis of AFBO (bioactivation) [11]. In a previous study, AFB1 increased significantly CYP3A28 mRNA level [43], and in our experimental conditions such an induction was counteracted by C, with a resulting significant gene downregulation.…”
Section: Drug Metabolism and Drug Transporterssupporting
confidence: 50%
“…As expected, several genes involved in drug metabolism and transport were affected by C pretreatment, thus demonstrating how C most likely affects AFB1 uptake and biotransformation. Cattle CYP3A28 (an orthologue of human CYP3A4 and the main CYP3A isoform expressed in BFH12 cells: [117]) is a key player in AFB1 metabolism, being responsible for the synthesis of AFBO (bioactivation) [11]. In a previous study, AFB1 increased significantly CYP3A28 mRNA level [43], and in our experimental conditions such an induction was counteracted by C, with a resulting significant gene downregulation.…”
Section: Drug Metabolism and Drug Transporterssupporting
confidence: 50%
“…Variations in NR ligand-binding domain sequences, differences in CAR/PXR-dependent transactivation of target genes (e.g., CYP2B ), as well as dose- and time-dependent differential responses, have been called into question to explain species differences in CYPs response to PB, PB-like compounds, and to a wider extent, prototypical CYP inducers [ 58 , 61 , 62 , 63 ]. With regard to cattle, the abovementioned hypotheses would be supported by results obtained in previously published in vitro/in vivo studies [ 44 , 64 , 65 , 66 ]. Additionally, the presence of alternative noncanonical NR (CAR) activation mechanisms (e.g., a PB-dependent increased phosphorylation-mediated signal regulation) have also been recently hypothesised [ 25 ].…”
Section: Discussionsupporting
confidence: 67%
“…The significant increase we observed in our experimental conditions suggested that cattle proteasome activity is activated in the presence of PB; moreover, it participated in targeting gene activation ( CYP2B22 and CYP3A28 at first) in response to CAR ligands and inducers such as PB, and likewise to humans [ 223 ]. Such a hypothesis is fascinating, but needs challenging molecular confirmatory studies (e.g., using 26S proteasome inhibitors) to confirm whether such a significant increase is either nonspecific and compensatory or a true biomolecular response to PB exposure, occurring through a 26S proteasome and CAR interaction, also in light of the controversial regulatory mechanisms hypothesized for bovine CYP3As and involving CAR and PXR [ 65 , 66 ]. Despite this, the present results represent one of the very few cases in which the proteasome activity was measured in domestic animals, and particularly in cattle; moreover, to the best of our knowledge, this was the first study in which the 26S proteasome activity was measured in bovines administered a prototypical DME inducer such as PB.…”
Section: Discussionmentioning
confidence: 99%
“…Very little information on the function of HNF4α was generated after those reviews. A recent study has found HNF4 binding sites in the proximal promoter of the cytochrome P450 3A gene in the bovine genome, suggesting that HNF4 might play a role in the response to xenobiotic [289]. While a complete picture of the ligands of HNF4 is not available, evidence in monogastrics supports a role of FA and acyl-CoA thioesters in the regulation of its activity: HNF4α was found to bind strongly to linoleic acid [290], as well as C17:0 cyclo, and, to a less extent, C16:0 [291].…”
Section: Hepatocyte Nuclear Factormentioning
confidence: 99%